Makna Manusia Menurut Paus Leo XIV dalam Ensiklik Magnifica Humanitas dan Relevansinya bagi Masyarakat Kontemporer - Agustinus Abraham (International Forum of Researchers and Lecturers, 2026)
The rapid development of digital technology and artificial intelligence has transformed human life in significant ways while simultaneously fostering a reductionist understanding of the human person based on productivity, efficiency, and technical capability. This phenomenon poses serious challenges to the understanding of human dignity and identity. This study aims to examine the concept of the human person according to Pope Leo XIV in the encyclical Magnifica Humanitas and to analyze its relevance for contemporary society. The research employs a qualitative method with a literature review approach, drawing primarily on the encyclical Magnifica Humanitas and related scholarly sources. The findings reveal that Pope Leo XIV understands the human person as created in the image and likeness of God (imago Dei), possessing an inherent dignity that does not depend on ability, social status, or productivity. This understanding is grounded in Christological and Trinitarian foundations, which affirm the human person as a relational being called to communion with God and others through love and self-giving. The encyclical also offers a critical response to technocratic paradigms, transhumanism, and posthumanism, which risk reducing human beings to technological objects or economic instruments. In the context of contemporary society, Pope Leo XIV’s thought provides a theological and ethical foundation for the development of human-centered technology while reinforcing respect for human dignity in social, educational, economic, and ecclesial life. This study concludes that the anthropological reflection presented in Magnifica Humanitas offers a significant contribution to addressing the human challenges emerging in the digital and artificial intelligence era.